1995
DOI: 10.1364/josab.12.001621
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of photorefractive subharmonics in the absence of wave mixing

Abstract: Using a new optical configuration free from the influence of photorefractive optical nonlinearity, we investigate the main characteristics of the spatial subharmonic K͞2 excited in a Bi 12 SiO 20 crystal by a light-intensity pattern with wave vector K and frequency V. It is shown that in a large region of intensity and applied electric field the optimum value V of the frequency corresponds to the conditions of parametric excitation of the weakly damped eigenmodes of the medium: the space-charge waves. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In many cases 1,10,13,[16][17][18][19] a lens has been used to focus the diffracted beams, thus making it impossible to judge their structure. Another interesting question is, Were the diffraction efficiencies of the subharmonic K/2 grating, obtained previously in the new configuration, 8,9 really a result of a single K/2 grating, or was it a narrow wave package centered at K/2? This question is important, as all theoretical modeling using the space-charge wave theory is based on the assumption that the subharmonic gratings are distinct and not packages.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In many cases 1,10,13,[16][17][18][19] a lens has been used to focus the diffracted beams, thus making it impossible to judge their structure. Another interesting question is, Were the diffraction efficiencies of the subharmonic K/2 grating, obtained previously in the new configuration, 8,9 really a result of a single K/2 grating, or was it a narrow wave package centered at K/2? This question is important, as all theoretical modeling using the space-charge wave theory is based on the assumption that the subharmonic gratings are distinct and not packages.…”
Section: Discussionmentioning
confidence: 98%
“…The generation of subharmonic K/2, K/3, and K/4 gratings then represent special cases in which k 1 or k 2 assumes an integer fraction of K. These statements were later supported by experiments performed in a new configuration in which optical beam coupling is avoided. 8,9 There it was demonstrated that the special case of K/2 subharmonic generation, in which the subharmonic grating has a spatial frequency of half the fundamental one, can take place. Moreover, many other features of the experiment seemed to agree well with the space-charge wave theory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,[6][7][8] One of the main assumptions in this theory is that the quality factor, which is the ratio of the eigenfrequency to the eigendamping, for the space-charge waves is much larger than 1. However, in spite of the large effort in obtaining agreement between theory and experiment, 3,[9][10][11][12] only a few investigations of the magnitude of the quality factor of the space-charge waves have been performed. Recently, Lyuksyutov et al 13 investigated the propagation of space-charge waves in space, where they screened a part of one recording beam, allowing the traveling space-charge wave to propagate freely into the shadow area.…”
Section: Introductionmentioning
confidence: 99%